Continuous flow membrane-less air cathode microbial fuel cell with spunbonded olefin diffusion layer - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2011)
The power production performance of a membrane-less air-cathode microbial fuel cell was evaluated for 53 days. Anode and cathode electrodes and the micro-fiber cloth separator were configured by sandwiching the separator between two electrodes. In addition, the air-facing side of the cathode was covered with a spunbonded olefin sheet instead of polytetrafluoroethylene (PTFE) coating to control oxygen diffusion and water loss. The configuration resulted in a low resistance of about 4 Omega and a maximum power density of 750 mW/m(2). However, as a result of a gradual decrease in the cathode potential, maximum power density decreased to 280 mW/m(2). The declining power output was attributed to loss of platinum catalyst (8.26%) and biomass growth (38.44%) on the cathode. Coulombic efficiencies over 55% and no water leakage showed that the spunbonded olefin sheet covering the air-facing side of the cathode can be a cost-effective alternative to PITE coating. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Diffusion; Impedance analysis; Oxygen transfer; Olefin sheet; PTFE; POWER-GENERATION; MARINE-SEDIMENTS; ELECTRICITY; PERFORMANCE; CATALYSTS; BINDERS; ENERGY